2014
DOI: 10.1007/s10029-014-1300-2
|View full text |Cite
|
Sign up to set email alerts
|

Totally endoscopic surgery on diastasis recti associated with midline hernias. The advantages of a minimally invasive approach. Prospective cohort study

Abstract: Totally endoscopic approach to diastasis recti associated with midline hernias is a feasible and reproducible method. It brings considerable esthetic advantages. Diastasis or hernia recurrences in medium term follow-up have not been observed. Diastasis greater than 6-7 cm or associated with severe musculoaponeurotic laxity of the abdominal wall could benefit from the use of reinforced prosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 15 publications
1
76
0
3
Order By: Relevance
“…The literature is limited. Six studies were identified: three prospective cohort and three retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature is limited. Six studies were identified: three prospective cohort and three retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…Endoscopic repair with plication of the diastasis using a non‐absorbable loop suture followed by an onlay or preperitoneal polypropylene mesh was performed of the midline hernia and the coexisting rectus diastasis in three studies. The studies of Köckerling and colleagues and Claus et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If RAD is symptomatic or associated with midline hernias (umbilical, trocar and/or epigastric), corrective surgery of all pathologies at the same time could represent the most recommended approach [3]. …”
Section: Introductionmentioning
confidence: 99%